The innate immune protein calprotectin ablates the bactericidal activity of β-lactam antibiotics - Amanda Z. Velez; Jana N. Radin; Emily N. Kennedy; Joshua B. Parsons; Heather M. Tong; Emma Jung; Emily Alam; Lauren C. Radlinski; Nikki J. Wagner; Vance G. Fowler Jr.; Sarah E. Rowe; Thomas Kehl-Fie; et al. (Proceedings of the National Academy of Sciences, 2026)
β-lactam antibiotics are among the most widely used treatments for bacterial infections, yet therapeutic failure is common even when no genetic resistance is detected. Understanding how host factors influence antibiotic efficacy is critical for improving outcomes. Here, we identify a host-derived mechanism of antibiotic tolerance mediated by calprotectin (CP), a zinc-binding protein released in large quantities by neutrophils during infection. We show that CP induces tolerance to β-lactam antibiotics in Staphylococcus aureus by chelating zinc and inactivating autolysins, zinc-dependent enzymes required for cell wall degradation and bacterial lysis following β-lactam treatment. This protective effect was specific to β-lactam antibiotics at concentrations of CP showing minimal impact on bacterial growth or metabolic state. Mechanistic studies revealed that CP inhibits the autolytic activity of Atl, the major S. aureus autolysin, by depriving the enzyme of its zinc cofactor. In a murine infection model, the efficacy of oxacillin was significantly enhanced in CP-deficient mice, demonstrating that CP impairs β-lactam activity in vivo. These findings reveal a form of immune-mediated antibiotic tolerance driven by metal sequestration and suggest that zinc availability at infection sites plays a critical role in shaping treatment outcomes.